Creation of a Prototype of a Multi-function Remote Presence Robot for Physical Research in Electronics - Beresnev, V. M.; Chekubasheva, V. A.; Glukhov, O. V.; Kravchuk, O. O. (My University, 2021)
The article presents methods for constructing and implementing an automated electronic system for collecting and analyzing information about various physical parameters of the environment under conditions of long-term continuous measurements. The system is based on microprocessor devices using wireless technologies with the implementation of the EKF SLAM algorithm for localizing places with an uneven distribution of environmental parameters to minimize pollution of cleanrooms. Also, it can then transmit signals through the operator's computer to the control elements of the room. Thus, the minimization of environmental factors for physical diseases and high-precision equipment is carried out, thereby extending its service life.
Keywords: Automated system; SLAM; Kalman filter; Infrared sensor; Robot; Cleanroom; Microclimate